A redistributive pattern at Assiut - Spalinger, Anthony John (JAOS)
The tomb of Ḏf(.ỉ)-Ḥʿpy at Assiut (No. 1) contains his well-known mortuary contracts that relate to the establishment of his cult. These contracts reveal various aspects of the role of the tomb owner and in particular demonstrate the bifurcation between office-held property and personal property, the latter of which is said to be derived from the paternal estate. In addition, the revenues that the tomb owner passed on to the priests associated with his cult divide themselves into two main sections: land and temple days which come from his paternal estate, and produce (including grains) which come from his office-held position. A flow chart outlining the economic transfers demonstrates the complexity of the system.